PENGARUH TINGKAT PEMAHAMAN WAJIB PAJAK, KUALITAS PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PRIBADI - Sutinah, Sutinah; Br. Purba, Neni Marlina (Aksara Public, 2020)
The purpose of this study was to determine the effect of the level of understanding of taxpayers, the quality of tax service and tax sanctions on personal taxpayer compliance registered at the South Batam Pratama Tax Office. The method in sampling uses accidental sampling. The population in this study was 75,192 people and sampling using accidental sampling, so that a sample of 100 people was obtained. Types of data using primary data by distributing questionnaires. Data collection techniques using descriptive analiysis techniques, data quality test (validity and reliability tests), classical assumption tests (normality test, multicollinearity test and heterokedasticity test) and multiple linier analysis. While the hypothesis test used partial test, simultaneous test and coefficient of determination test. Partial test results the level of understanding of taxpayers has a significant effect on compliance with personal taxpayers. The quality of tax services has a significant effect on compliance with personal taxpayers. Tax sanctions have a significant effect on compliance with personal taxpayers. Simultaneous test results of tax compliance, tax service quality and tax sanctions simultaneously have a significant effect on taxpayer compliance. Determination test results obtained a value of 0,472 which means the level of tax compliance, tax service quality and tax sanctions influence 47,2% of personal taxpayer compliance, while the remaining 52,8% is influence by other variables outside this study.